Plasminogen/plasmin influence on platelet aggregation - Roka-Moya, Y.M.; Zhernossekov, D.D.; Grinenko, T.V. (Вiopolymers and Cell, 2012)
Aim. Determination of the influence of Glu- and Lys-plasminogen/ plasmin on the platelet aggregation induced by different agonists. Methods. Platelet aggregometry. Spectrophotometry. Results. We have shown the inhibitory effect of Lys-plasminogen on human platelet aggregation. The pro-enzyme action is related to the second wave of aggregation. The inhibitory effect of Lys-plasminogen possesses dosedependent manner in case of thrombin-induced aggregation. The inhibitory effect of pro-enzyme with ristocetin as an inductor has not been observed. Glu-plasminogen and plasmin do not influence on platelet aggregation under studied conditions. A serine protease inhibitor aprotinin does not change the inhibitory effect of Lys-plasminogen. Conclusions. The results proved the inhibitory effect of Lys-plasminogen on thrombin- and collagen-induced platelet aggregation. The absence of inhibitory effect of Lys-plasminogen in the case of ristocetin-induced aggregation leads us to conclusion, that GP Ib/IX is not involved into the inhibited aggregation pathway. The unchanged inhibitory effect of Lys-plasminogen in the presence of aprotinin excludes plasmin participation in the inhibitory phenomenon.
Keywords: platelet aggregation, plasminogen, plasmin. Мета. Визначити вплив Глу- і Ліз-форм плазміногену та плазміну на агрегацію тромбоцитів, індуковану різними агоністами. Методи. Агрегатометрія. Спектрофотометрія. Результати. Отримано дані щодо інгібувального впливу Ліз-плазміногену на агрегацію відмитих тромбоцитів людини. Дію проферменту спостерігали на другій хвилі агрегації тромбоцитів. Показано дозозалежний характер його інгібувального ефекту на агрегацію тромбоцитів, стимульованих тромбіном. Ристоміцин-індукована агрегація не пригнічується Ліз-плазміногеном. Глу-плазміноген і плазмін не впливають на функціональні властивості клітин за умов експерименту. Інгібітор серинових протеїназ апротинін не впливає на ефект інгібування агрегації Ліз-плазміногеном. Висновки. Вперше встановлено інгібувальний вплив Ліз-плазміногену на агрегацію тромбоцитів, стимульованих тромбіном і колагеном. Відсутність дії проферменту на агрегацію, індуковану ристоміцином, вказує на те, що Ліз-плазміноген не впливає на ланку агрегації, яка реалізується за участі ГП Іb/IX. Інгібування Ліз-плазміногеном агрегації тромбоцитів за присутності апротиніну робить неможливою участь плазміну в реалізації інгібувального ефекту зимогену.
Ключові слова: агрегація відмитих тромбоцитів, плазміноген, плазмін. Цель. Изучить влияние Глу-, Лиз-форм плазминогена и плазмина на агрегацию тромбоцитов, индуцируемую различными агонистами. Методы. Агрегатометрия. Спектрофотометрия. Результаты. Получены данные об ингибирующем влиянии Лиз-плазминогена на агрегацию отмытых тромбоцитов человека. Действие профермента проявлялось во время второй волны агрегации. Показан дозозависимый характер его ингибирования агрегации тромбоцитов, стимулированных тромбином. Ристомицин-индуцированная агрегация не подавляется Лиз-плазминогеном. Глу- плазминоген и плазмин не влияют на функциональные свойства клеток в условиях эксперимента. Ингибитор сериновых протеиназ апротинин не изменяет характера ингибирования агрегации Лиз-плазминогеном. Выводы. Впервые установлен ингибирующий эффект Лиз-плазминогена на агрегацию тромбоцитов, стимулированных тромбином и коллагеном. Отсутствие влияния профермента на ристомицинндуцированную агрегацию указывает на то, что Лиз-плазминоген не действует на путь агрегации, реализуемый при участии ГПІb/IX. Ингибирование Лиз-плазминогеном агрегации тромбоцитов в присутствии апротинина исключает участие плазмина в реализации ингибирующего эффекта.
Ключевые слова: агрегация отмытых тромбоцитов, плазминоген, плазмин.